"Alexafying" shoppers: The examination of Amazon's captive relationship strategy. (September 2021) - Ramadan, Zahy B.
Abstract: The virtual assistants' market is drastically growing and is expected to reach 2.1 billion by 2020. Nonetheless, the quick expansion and high penetration of e-retailers' AI ecosystem into the shopper's journey is still under-researched in the extant literature. Amazon's Alexa in particular has been fast proliferating into the customer's journey, favoring the development of captive audiences given this new ambient environment. Through a mixed methodology using both qualitative and quantitative approaches, this study examines Amazon's captive relationship strategy on shoppers, brands and competing retailers. The research findings show that Amazon's AI relationship strategy with its customers is based on forming a multi-faceted identity for the AI that would later on facilitate a captive situation that would lead to an addictive relationship. This study is amongst the first to examine the rapid development of e-retailers' AI ecosystem into the shopper's journey. Taking the pioneering case of Amazon's Alexa powered devices, this research presents a working framework upon which scholars and practitioners alike could base their future studies and strategies on in the fast-growing field of interactive voice assistants and AI led conversations. Graphical abstract: Image 1